Twice shy - Francis, Dick. (New York : Putnam, 1982)
A surefire computerized betting system draws desperate men who will do anything to gain control of it.
Booklist.
Wilson's Fiction.
Young Adult.
Young Adult
Keywords: Horse racing -- Fiction; Detective and mystery stories